The ultimate guide to weight training for track and field - Price, Robert G., ....- (2007)
The Ultimate Guide to Weight Training for Track and Field is the most comprehensive and up-to-date track and field-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round track and field-specific weight-training programs guaranteed to improve your performance and get you results. Athletes of all events, from sprinting to shot put, have used and benefited from the information in this text. No other track and field book to date has been so well designed, so easy to use, and so committed to weight training. This book will have all types of track & field athletes increasing speed, flexibility, power, strength, and endurance unlike any book before it. No longer will you find yourself becoming tired at the end of an event or losing distance on javelin or discus throws due to fatigue. By following this program you will eclipse your previous records and eliminate unnecessary injuries. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!
Maximize your athletic potential! - sport-specific programs designed to: run faster, throw faster, jump higher, and prevent injuries
Keywords: Atletiek ; krachttraining